Hyperosmolarity impedes the cross-priming competence of dendritic cells in a TRIF-dependent manner - Zoran V. Popovic (Nature Portfolio, 2017)
Abstract Tissue osmolarity varies among different organs and can be considerably increased under pathologic conditions. Hyperosmolarity has been associated with altered stimulatory properties of immune cells, especially macrophages and dendritic cells. We have recently reported that dendritic cells upon exposure to hypertonic stimuli shift their profile towards a macrophage-M2-like phenotype, resulting in attenuated local alloreactivity during acute kidney graft rejection. Here, we examined how hyperosmotic microenvironment affects the cross-priming capacity of dendritic cells. Using ovalbumin as model antigen, we showed that exposure of dendritic cells to hyperosmolarity strongly inhibits activation of antigen-specific T cells despite enhancement of antigen uptake, processing and presentation. We identified TRIF as key mediator of this phenomenon. Moreover, we detected a hyperosmolarity-triggered, TRIF-dependent clustering of MHCI loaded with the ovalbumin-derived epitope, but not of overall MHCI molecules, providing a possible explanation for a reduced T cell activation. Our findings identify dendritic cells as important players in hyperosmolarity-mediated immune imbalance and provide evidence for a novel pathway of inhibition of antigen specific CD8+ T cell response in a hypertonic micromilieu.